Trunk orthosis with joints providing resistive force improves dynamic sagittal alignment in postoperative patients with lumbar spinal stenosis - Tatsuya Igawa; Ken Ishii; Junji Katsuhira; Akifumi Suzuki; Hideto Ui; Ryunosuke Urata; Norihiro Isogai; Yutaka Sasao; Ko Matsudaira; Haruki Funao (Scientific Reports, 2023)
Abstract This study aimed to determine whether a trunk orthosis with joints providing resistive force (TORF) modifies sagittal malalignment during level walking in patients with lumbar spinal stenosis (LSS). Fifteen patients, 6 months after undergoing surgery for LSS, performed level walking at a self-selected speed while wearing a TORF. Dynamic sagittal alignment, including sagittal vertical axis, lumbar lordosis, and pelvic tilt, and spatiotemporal data as well as lower limb kinematic and kinetic data were recorded using a three-dimensional motion analysis system and six force plates. Statistical analysis was performed to compare these data with and without the TORF, respectively. Compared to the condition without the TORF, the use of the TORF significantly decreased positive sagittal vertical axis (p < 0.05) and increased the lumbar lordosis and pelvic tilt (p < 0.05). Peak hip flexion angle and extension moment during loading response (LR) significantly increased (p < 0.05), and peak hip extension angle and flexion moment during PS statistically decreased (p < 0.05). There was no difference in spatiotemporal data between the two conditions. Our findings suggest that TORF may modify the dynamic sagittal global alignment and lower limb kinematic and kinetics in postoperative LSS patients during level walking.